ANALISIS POTENSI GOLPUT PADA PEMILU 2014 DI KOTA YOGYAKARTA - Mustadin Mustadin (UIN Sunan Kalijaga, 2013)
The number of abstentionsin the city of Yogyakarta was the biggest in the province of Yogyakarta In election 2009.The result showed the level of non-voters in the city of Yogyakarta was 34%. Abstentions in Yogyakarta occurred tendency increasingly in every election in Indonesia. Therefore, this study try to exploring and reading on the causes and potential abstentions in the2014 general election in Yogyakarta. This study used qualitative research methods. This research tries to explore the phenomenon of non-voters with a theoretical approach, and then this research explored the phenomenon of non-voters within-depth interviews for Ellection Commision of Yogyakarta (KPU). The results showed there are several factors inﬂuenced non-voters in the city of Yogyakarta. First; Technical factors, the example is sickness of voters when the election process. Second,Job factor or voter’s daily activities.Third; administrative factoris a factor related to the administrative aspects of the resulting voters could not exercise their voting rights.